Aprovechamiento del recurso forestal maderable y la sostenibilidad de la actividad forestal en Loreto: el caso de la Empresa Lisbeth & Diego Forestales E.I.R.L, 2022 - Noriega Cumari, Jorge Gian Poll (2022)
The study was carried out in the Forest Concession of the LISBETH & DIEGO FORESTALES E.I.R.L Company located in the white-water ravine in the Momón River Basin, tributary on the left bank of the Nanay River, Punchana District. In order to demonstrate whether the harvesting activities of forestry companies in the Loreto region are sustainable, in a case study with the company LISBETH & DIEGO FORESTALES E.I.R.L. The study is applicative of explanatory level and quantitative approach. It is non-experimental, transversal. The study sample is defined by twenty (20) people, including owners, administrative and field staff. Data was collected through documentary analysis and questionnaire (survey). All the information was processed in Excell, the statistical analysis with INFO STAT and the Chi square test was used for the inference analysis. Which allowed to conclude according to the level of significance of the Chi square test, the null hypothesis is rejected and the alternative hypothesis is accepted, concluding that the sustainability of the forestry activity in the Loreto region is not guaranteed with the application and compliance of the Forestry and Wild Fauna Law, other factors are necessary, which is demonstrated with the Correlation test where, according to the results found, the null hypothesis is not met, since there is a high degree of significance between sustainability forestry and the law that regulates the activity.